PENGARUH TATA KELOLA PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2015-2016) - Risyad Kurnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aimed to obtain empirical evidences regarding the impact of GoodCorporate Governance and Profitability on the firm’s value reflected in Tobin’s Qvalue. A firm’s Good Corporate Governance was determined using several variablesincluding the size of board committee, the proportion of independent board ofcommissioners, and the number of audit committee, while the profitability wasmeasured by net profit margin and return on assets. The population of this research ismanufacturer firms registered in Indonesia Stock Exchange on 2015-2016. The samplesize of this study was 119 firms with two years surveillance, hence, the total samplesstudied were 238 firms. Data analysis was performed using classic assumption test andhypothesis testing was performed using Double Linear Regression analysis. The resultof this study showed that the board size, proportion of independent board ofcommissioner, and return on asset had a positive impact on the firm’s value, while thenumber of audit committee and net profit margin did not have impact on the firm’svalue,.Keywords: Board Size, Proportion of Independent Commisary, Number of AuditCommittee, Net Profit Margin, Return on Asset, Tobin’s Q.